(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research is an analytical study of one of the well-known poet of Kurdish literature, Piramerd’s poetry and maxims. In which his moral, religious, and critical perspectives toward the Jewish nation are revealed. In this research, the poet’s view towards Jewish behavior with humanity and their attitude patterns from moral and religious standpoints are discussed and analyzed. Piramerd, by relying on his Islamic and religious knowledge, has criticized certain behaviors and attitudes specific to this nation. Characteristics, which in his opinion, have hindered proper co-existence with other nations. Furthermore, the content of “yahudi morality” is discussed from historical, religious, and moral viewpoints. Additionally, the Jewish nation, because of geographical and cultural dispersion, has been recognized as possessing similar behavioral characteristics referred to as “Jewish behavior” a concept characterized by several criticized traits such as: national superiority complex, covenant-breaking, dishonesty, troublemaking, and materialism. Subsequently, he worked on the etymological foundations of the word “yahudi” which was examined from a historical perspective, derived from the combination of the word “yahu” meaning God, and “di” meaning acknowledgment or reward. Over time and throughout history, the word “Jewish” has taken on various social and historical meanings, and connotations, specifically in Greek, Roman, and medieval European cultures, where it sometimes appeared with negative meanings like: merchant, materialist, or deceiver.